2022
DOI: 10.1002/cctc.202200297
|View full text |Cite
|
Sign up to set email alerts
|

Selective Demethoxylation of Guaiacols to Phenols using Supported MoO3 Catalysts

Abstract: Lignin‐derived monomers with methoxy substituents are abundantly present in bioliquids derived from lignocellulosic biomass. Examples are the products obtained from the reductive catalytic fractionation of lignin (RCF) and pyrolysis of lignocellulosic biomass and hydrotreated products thereof. An attractive valorization step for these liquids involves demethoxylation to obtain alkylated phenols through selective catalytic hydrodeoxygenation (HDO). Within the context of sustainable chemistry, there is a strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…However, only 4-propylphenol was observed in this study and 2-methoxy-4propylcyclohexanol was not detected under any of the tested conditions including a low reaction temperature and short reaction time, implying that 4PG was first converted to 4propylphenol via demethoxylation (Rxn.1). This can be explained by the metal-support interaction effect of TiO2 and Co that created the Ov sites to bind with oxygen atoms in the substrates, leading to the selective demethoxylation from among the various other possible reaction pathways [65]. This agrees with an earlier finding that adding TiO2 to a Pd/SiO2 catalyst improved demethoxylation [69].…”
Section: Proposed Reaction Pathwaysupporting
confidence: 89%
See 1 more Smart Citation
“…However, only 4-propylphenol was observed in this study and 2-methoxy-4propylcyclohexanol was not detected under any of the tested conditions including a low reaction temperature and short reaction time, implying that 4PG was first converted to 4propylphenol via demethoxylation (Rxn.1). This can be explained by the metal-support interaction effect of TiO2 and Co that created the Ov sites to bind with oxygen atoms in the substrates, leading to the selective demethoxylation from among the various other possible reaction pathways [65]. This agrees with an earlier finding that adding TiO2 to a Pd/SiO2 catalyst improved demethoxylation [69].…”
Section: Proposed Reaction Pathwaysupporting
confidence: 89%
“…These results imply that the Co/TiO2-R catalyst had a higher activity than the Co/TiO2-A catalyst to promote the HDO of 4PG. This was attributed to the greater number of Ov formed on the surface of TiO2-R, as supported by the XPS analysis, which then facilitated C-O bond scission and selective demethoxylation [65].…”
Section: Effect Of the Reaction Temperature And Reaction Timementioning
confidence: 80%
“…Finally, in 2022, selective MoO 3 /TiO 2 catalyzed hydrodemethoxylation of pyrolysis oil rich in guaiacols was described by Heeres. 136 Hydrodemethoxylation of models guaiacol and 4-propylguaiacol over 5 wt% MoO 3 /TiO 2 gave 82% and 72% selectivity to phenols at 97% and 90% conversion, respectively. Application of the method to pyrolysis oil rich in guaiacol, 4-methylguaiacol and 4-ethylguaiacol as major compounds (350 °C under 20 bar H 2 pressure) provided high conversion of methoxylated substrates, delivering the corresponding alkylphenols in >85% combined selectivity (Table 2).…”
Section: Defunctionalization: C(aryl)–o To C(aryl)–hmentioning
confidence: 99%
“…Demethoxylation is to remove the methoxyl groups in lignin, and then generates available sites adjacent to the phenol hydroxyl group. 138,139…”
Section: Synthesis Of Lprmentioning
confidence: 99%
“…Demethoxylation is to remove the methoxyl groups in lignin, and then generates available sites adjacent to the phenol hydroxyl group. 138,139 Huang et al reported an approach that converts a lignin monomer into phenol based on a combination of selective demethoxylation with transalkylation of the alkyl groups. 140 They demonstrated that intimate contact between a TiO 2 -supported Au nanoparticle catalyst for demethoxylation and an HZSM-5 transalkylation catalyst can result in a phenol yield of nearly 60%.…”
Section: Synthesis Of Lpr From Modified Ligninmentioning
confidence: 99%